THE PROBLEM OF INVESTMENT ATTRACTIVENESS OF THE NATIONAL ECONOMY OF THE REPUBLIC OF MOLDOVA - Angela ȘESTACOVSCAIA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This article addresses the issue of investment attractiveness at the macroeconomic level. Some definitions of this economic category are given. In practical aspect, the author envisages the state of the investment environment in the Republic of Moldova of two three-year periods, covering three years of implementation of the National Strategy to attract investments and promote exports for the period 2016-2020 and three previous years. The structure of investments in long-term tangible assets, in the context of terms of ownership, sources of financing, types of activity is studied in detail. Special influence is given to foreign direct investment, its dynamics for the period of the last three years and in comparison with their values described in the above-mentioned strategy. The investment quote per head of population in the Republic of Moldova and in neighbouring countries Ukraine and Romania is reported. The results of the Doing Business report are presented, showing the place of the Republic of Moldova in the international rating, which includes 190 countries. The most attractive spheres for foreign capital are considered banking system and re-employment industry, as well as the reasons for this interest are indicated. The main problems that limit the inflow of investments into the economy of our state have been identified, the elimination of which would contribute to improving the investment climate in the country and increasing investment attractiveness.